Audit Expectation GAP in The Public Sector of The Gambia - Saikou Conteh; Hamidah Hamidah (The Indonesian Accounting Review, 2021)
In the private sector, the audit expectations deficit is a big concern. The audit expectations divide, on the other hand, is a new problem in the public sector that has received little attention from researchers. Just a few studies on the audit expectations deficit in the public sector have been conducted so far in the sense of financial audit. In the background of the above, this study centered on the audit expectations difference. The study was motivated by the importance of the financial audit feature in the Gambian public sector, as well as recent developments related to this type of audit in the country (such as rising expectations among users and associated problems in practice). As a result, the study aims to assess whether or not there is a difference in audit expectations in the Gambian public sector. According to the results of this report, there is an audit expectations deficit in the Gambian public sector when it comes to performance auditing. Interviews indicate that there is a broad gap in audit standards on several auditing topics. These include fraud detection exercises, management, executive and other parties' impact on auditors, audit report format, and widening the audit mandate to include policy merits.